Controlling Functional Complexity for Overfitting Avoidance in Genetic Programming - Magessi, Inês Marcão Cortes (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science